ANALISIS KEBUTUHAN PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS PROBLEM BASED LEARNING TENTANG MATERI KEANEKARAGAMAN HAYATI UNTUK KELAS X SMA/MA - Arsih, Fitri; Devi, Sarada (Universitas Cokroaminoto Palopo, 2025)
The development of LKPD for biology learning needs to be conducted so that the biology learning process can train students' critical thinking skills in problem-solving. This study aims to identify the needs for LKPD based on Problem-Based Learning (PBL), which will be developed as teaching materials to support students' critical thinking skills in biology learning, especially in the topic of biodiversity. The method used in this study is qualitative, with a descriptive approach. The subjects used were 30 students from class X MIPA 1 of State Senior High School 2 Sungai Limau. Data collection was conducted in two ways: observational surveys of students and interviews with teachers. Meanwhile, the instruments used were questionnaire sheets and interviews. Through data collection, it was found that learning based on Problem Based Learning (PBL) had not been implemented and there was no LKPD model of PBL-based learning, especially on biodiversity material. Therefore, it is necessary to develop LKPD based on PBL on biodiversity material for grade X of high school.